Tuberculous meningitis, an unusual presentation in a young lady. (9th July 2012) - Chohan, Tanveer; Jain, Arihant; Saeed, Marwa; Saeed, Saad Aldeen; Dharmasena, Upul Kumara
Abstract : A 37-year-old Persian-speaking woman presented with epigastric pain, vomiting and non-specific frontal headache. Examination was unremarkable except for an isolated sixth nerve palsy found a few days after admission. Blood results were normal, as was the chest radiograph and the CT scan of the head. Initial cerebrospinal fluid (CSF) analysis revealed a significantly elevated protein level with reduced glucose, as well as CSF lymphocytosis. Tuberculosis (TB) meningitis was considered and she was commenced on anti-TB treatment before confirmation of the diagnosis. A full contact tracing was performed with regular follow-up with TB nurses. When she was seen in the clinic a month later, her symptoms had subsided completely.